Competitive mimicry: The socialization of antifeminist NGOs into the United Nations - Jelena Cupać; Irem Ebetürk (Global Constitutionalism, 2022)
Conservative NGOs contesting women's rights in the United Nations are on the rise, and their activity is increasingly described as an antifeminist backlash. This article focuses a new theoretical lens on this development: socialization. It argues that conservative NGOs' socialization into transnational practices and the United Nations has played a significant part in facilitating the antifeminist backlash. To support this claim, the article examines socialization comprehensively, applying several analytical angles: its definition, directionality, mechanism, degree and effects. It also treats conservative NGOs' socialization as both a process and an outcome. As a process, it unfolds horizontally, by conservative NGOs competitively mimicking feminist NGOs in two domains in particular: their manner of transnational organizing and their skilful use of the UN human rights framework. The article finds that conservative NGOs have socialized into transnational NGO practices and the regulative institutional rules of the United Nations, but not into all its constitutive norms. The chief effect of this kind of socialization is polarization. The article singles out and empirically illustrates three of its manifestations: the struggle for institutional spaces; zero-sum politics based on a sense of existential threat; and the use of a strong moralizing discourse.
Keywords: 300; antifeminist backlash; moralizing discourse; NGOs; polarization; socialization; United Nations